Sample development and introduction layer for dry slides
Patent Information
- Application Number
- JP2026516171
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-14
- Filing Date
- 2024-09-16
- Publication Date
- 2026-10-14
Smart Images

Figure 2026534085000006 
Figure 2026534085000007 
Figure 2026534085000008
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a highly reflective, low-density, permeable spreading layer for the transport, handling, and analysis of fluids, including the clinical analysis of biological fluids. [Background technology]
[0002] Analytical assays and analyses are generally performed with many types of liquid samples, including aqueous biological fluids such as blood, plasma, serum, urine, and cerebrospinal fluid. While wet chemistry-based techniques, where the reaction reagents are in liquid form, are used in many analytical assays, dry chemistry, where the reagents are present in a dry form, for example, in one or more layers on a reaction vessel or support, has been established to meet many laboratory needs, such as providing accurate and reproducible results quickly with minimal operator involvement and minimal sample volume.
[0003] To obtain optimal results, layer-based dry chemistry requires effective spreading and distribution of the sample applied to the layers so that, as the sample moves to one or more layers below the application layer, the exposure of one or more analytes in the sample to any reagents present in the layers becomes uniform. The layers that receive the sample and then spread and distribute it to the layers below must be permeable, i.e., have pores through which the sample can flow.
[0004] In order to create a permeable (i.e., porous) layer that spreads, distributes, and transmits the sample to the lower layer, particulate matter is often combined with a binder and deposited as a layer. Polymer particles have compatibility with the binder system and an appropriate density (approximately 1 g / cm³). 3 ), and are most commonly used for their controlled particle size and particle size distribution. However, polymer particles have drawbacks, including low reflectivity, lack of mechanical robustness in the fabrication of layers, and environmental concerns.
[0005] Minerals (e.g., TiO2, BaSO4, CaCO3) and other non-organic particles, including solid glass spheres, have been used in the developing layer. Some of these particles offer functional benefits, such as high reflectivity for TiO2, but they also present challenges in terms of manufacturing (e.g., poor coating properties and process control due to small particle size and high density). Mixtures of inorganic pigments and polymer particles are commonly used in attempts to balance the disadvantages of each with the resulting mixture. [Overview of the project]
[0006] This disclosure provides a permeable deployment layer that effectively distributes and transports aqueous samples while also possessing, for example, substantial reflectivity, resistance to mechanical failure, and inducement to the formation of a uniform layer during manufacturing, thereby minimizing or eliminating environmental concerns.
[0007] This disclosure provides permeable deployable layers for the transport, manipulation, and analysis of fluids, including the clinical analysis of biological fluids. One aspect of this disclosure provides a permeable deployable layer comprising hollow glass microspheres and a polymeric binder, wherein the polymeric deployable layer has high reflectivity and low density. In some embodiments, the polymeric binder comprises an emulsifying polymer or copolymer having adhesive properties. In certain embodiments, the dry reflectivity, wet reflectivity, or both are high, and in embodiments, higher than known deployable layers.
[0008] In some embodiments, the permeable developing layer further comprises one or more additional components, including buffers, surfactants, plasticizers, biocides, defoamers, pigments, and void-forming agents. [Brief explanation of the drawing]
[0009] Other features, purposes, and advantages not mentioned above will become clearer when considering the detailed explanation below. Refer to the following diagram for this detailed explanation.
[0010] [Figure 1] This shows a TEM image of a cross-section of a slide with a sample introduction and development layer (SLS) as the uppermost layer. [Figure 2] This shows a top-down TEM image of a slide with a sample introduction and development layer (SLS) as the uppermost layer. [Figure 3] This graph shows the incremental intrusion amount versus pore size when using mercury intrusion porosimetry in the embodiments of this disclosure. [Figure 4] This diagram shows the logarithmic differential intrusion amount versus pore size when mercury intrusion porosimetry is used in the embodiments of this disclosure. [Figure 5] The graph shows the incremental intrusion amount versus pore size when mercury intrusion porosimetry is used in the control embodiment. [Figure 6] The graph shows the logarithmic derivative of the intrusion amount versus pore size when mercury intrusion porosimetry is used in the control embodiment. [Figure 7] This graph shows the average absolute reflectance of a coated uncoated layer containing hollow glass microspheres (solid line) compared to a coated uncoated layer containing cross-linked polystyrene microspheres (dashed line). [Modes for carrying out the invention]
[0011] While the methods and compositions described herein are susceptible to various modifications and alternative forms, exemplary embodiments are shown in the drawings and described in detail herein. However, it should be understood that the description of exemplary embodiments is not intended to limit the apparatus and methods to any particular form disclosed, but rather to encompass all modifications, equivalents, and alternatives that fall within the spirit and scope of the apparatus and methods defined herein and in the following claims. Therefore, various aspects and embodiments of this specification and in the following claims should be referenced in order to interpret the scope of the apparatus and methods.
[0012] explanation This specification provides a permeable developing layer for the transport, manipulation, and analysis of liquids. The permeable developing layer is a layer capable of receiving a liquid sample, whether applied directly to the permeable developing layer (e.g., by a user or an automated sample analyzer) or supplied to the developing layer from a layer in fluid contact with the developing layer. Within the permeable developing layer, the liquid sample is distributed such that a uniform apparent concentration of each substance in the sample is provided on the surface of the layer in fluid contact with the permeable developing layer. Such apparent concentrations can be achieved through the thickness of the permeable developing layer or by a concentration gradient present within the permeable developing layer in other ways. Such gradients can be adapted using known calibration techniques without any difficulty in obtaining quantitative test results.
[0013] Some terms are introduced below.
[0014] In this specification, “sample” and “liquid sample” refer to a fixed, cohesive volume of fluid for analysis using dry chemistry. The fluid may be treated before dry chemistry analysis (e.g., by absorption, adsorption, chromatography, distillation, extraction, ion exchange, filtration, complex formation, crystallization, centrifugation, drying, dissolution, replenishment, etc.). “Sample” includes pre-treated or untreated fluid applied directly by the user or an automated sample analyzer to a permeable developing layer or dry chemistry analysis element (comprising two or more layers, one of which is the permeable developing layer of this disclosure). The sample also includes fluid passing from one layer to another within the dry chemistry analysis element. The sample may include one or more “substances,” such as analytes, reagents, precursors, cofactors, enzymes, catalysts, non-enzymatic proteins, buffers, salts, etc., any of which may facilitate, hinder, or have no effect on the analysis of the fluid.
[0015] The term "approximately" means plus or minus 10% of the listed measurements. Unless otherwise specified, for any range specified using the word "approximately," "approximately" applies to both ends of the range, whether specified or not. For example, "approximately 87% to 97%" is equivalent to "approximately 87% to approximately 97%."
[0016] The recitation of ranges of values in this specification is merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, unless otherwise indicated herein, and each separate value is incorporated into this specification as if it were individually recited. For example, when a concentration range is stated as 1% to 50% (or degrees, amounts by mass, etc.), values such as 2% to 40%, 10% to 30%, or 1% to 3% are expressly enumerated in this specification. These are only examples of what is specifically intended, and all possible combinations of numerical values between the enumerated minimum and maximum values and numerical values including those minimum and maximum values are deemed to be explicitly stated in the present disclosure.
[0017] Aspects and embodiments of a permeable spreading layer are disclosed herein. In one aspect, the present disclosure provides a permeable spreading layer comprising hollow glass microspheres and a polymeric binder. In embodiments, the polymeric spreading layer has high reflectivity and low density, and in embodiments, the polymeric binder comprises an emulsion polymer or copolymer having adhesive properties. Further embodiments and features of the permeable spreading layer of the present disclosure are as follows.
[0018] In some embodiments, the permeable spreading layers herein are "isotropically permeable" or "isotropically porous", while in some embodiments, the permeable spreading layers herein are anisotropically permeable or porous. These terms refer to the regularity of porosity in all directions within the structure of the permeable spreading layer.
[0019] In one aspect, particulate materials can be used to form such a permeable spreading layer and provide porosity, where the porosity is created by interconnected spaces between particles. Various types of particulate matter have been previously used, including pigments (e.g., titanium dioxide, barium sulfate, zinc oxide, etc.), diatomaceous earth and microcrystalline colloidal materials (e.g., microcrystalline cellulose), as well as spherical particles of uniform size (e.g., polymer beads). However, in some embodiments herein, hollow glass microparticles or microspheres ("HGM") are the primary particulate material used in the permeable spreading layer. Hollow glass microspheres may also include different types of glass, such as soda-lime glass, borosilicate glass, lead glass, aluminosilicate glass, oxide glass, glass-ceramic glass, non-silicate glass, and polymer glass, as well as other materials having physical properties (e.g., density, reflectivity) similar to hollow glass microspheres, and combinations thereof. Additional relevant disclosures are provided elsewhere herein.
[0020] The degree of porosity can vary depending on, for example, pore or void size, pore or void volume, or other parameters. The interconnected void spaces present between adjacent particles of the permeable spreading layer provide for liquid transport, for substances contained in the sample, or for substances introduced into the sample to be transported through the structure.
[0021] The void spaces within the permeable spreading layer represent a void volume in the range of about 10 to 80 percent. Where it is desirable to increase the void volume, the spreading layer can comprise a particulate structure having a void volume in the range of about 40 to 80 percent. In embodiments, the average void volume of the polymer spreading layer accounts for about 10 percent to about 80 percent, about 20 percent to about 80 percent, about 30 percent to about 80 percent, or about 40 percent to about 80 percent. The presence of these interconnected void spaces provides a path through which a fluid sample can flow.
[0022] The average size of the void spaces in this disclosure is small in absolute terms, but relatively large at the molecular scale. The effective average void size shown by the permeable unfolding layer of this disclosure is typically within about 0.01 to 1 times the average particle size of the hollow glass microspheres used to fabricate the permeable unfolding layer. Thus, liquid transport is facilitated by the capillary action of the liquid drawn out through these interconnected spaces within the particle structure of the unfolding layer. In some embodiments, the median pore or void size is about 0.1 to 50 μm. In some embodiments, the median pore or void size is about 0.1 to 25 μm. In some embodiments, the median pore or void size is about 1 to 50 μm. In some embodiments, the median pore or void size is about 1 to 25 μm.
[0023] The size and volume of the void spaces in particulate structures can vary considerably and depend on many factors, including the size of the hollow glass microspheres contained in the structure, the method of preparing the structure, and the presence and size of additional particulate matter.
[0024] For example, in some embodiments including hollow glass microspheres and one or more additional particulate materials, such as pigments, the average size of the void spaces is affected by the average particle size of the hollow glass microspheres and the one or more additional particulate materials. That is, the average void space size of a permeable development layer made with hollow glass microspheres with an average diameter of 60 microns is typically smaller when compounded with additional particles having an average diameter of 10 microns. Further details regarding these various parameters are presented elsewhere in this specification. In any given development layer, the desired size of these void spaces depends on the specific liquid sample being transported. That is, the viscosity of the sample, as well as the size and molecular properties of various substances originally contained in or introduced into the sample, affect the selection of an appropriate void space size.
[0025] The size of the void spaces within particulate structures can be measured by conventional techniques, including, in particular, gas sorption, liquid injection (e.g., mercury injection), X-ray and neutron scattering, and microscopic morphology.
[0026] In some embodiments, the permeable developing layer develops the sample in two dimensions along the plane of the developing layer. For example, if a sample with a droplet diameter of 3 mm is applied from the pipette tip to the first side of the developing layer, the developing layer can increase the area of the sample that appears from the second side opposite the developing layer. For example, the area of the applied sample can be increased by, for example, 2 to 100 times. In some embodiments, the area of the sample applied on the first side can be increased by about 4 to 50 times, and in some embodiments, the area of the sample applied on the first side can be increased by about 4 to 20 times.
[0027] In some embodiments, the permeable developing layer mixes the material in the sample as it passes from a first side of the developing layer to a second side opposite the developing layer. For example, if a heterogeneous sample is applied to the first side of the developing layer, the developing layer can reduce the heterogeneity of the sample appearing from the second side opposite the developing layer.
[0028] In some embodiments, the permeable spreading layer of the Disclosure can measure or distribute an applied sample. That is, the spreading layer receives an applied liquid sample on a first surface and distributes the sample within itself, thereby providing a uniform concentration of the liquid sample and the substances contained therein to the opposite surface of the spreading layer. In some embodiments, it is possible to obtain a substantially uniform concentration over a range of volumes of the applied sample, so high-precision sample application techniques are not required.
[0029] The dry thickness of the permeable development layer can vary considerably depending on the size of the hollow glass microspheres and the specific intended use of the development layer. In embodiments including a support structure for the permeable development layer, the dry thickness of the permeable development layer is in the range of about 100 to about 400 microns. However, for specific applications, structures with thicknesses outside the aforementioned range may also be used.
[0030] Unmodified hollow glass microparticles typically do not naturally adhere to each other or to adjacent layers, for example, in a dry chemical analysis element. When particulate matter does not adhere, it can be treated to obtain particles that can adhere to each other at contact points, thereby promoting the formation of a permeable unfolding layer. As an example of appropriate treatment, non-adherent particles can be coated with a thin adhesive layer, such as a polymer binder, and formed into a layer. Once the binder coating dries, the integrity of the layer is maintained, and open void spaces remain between its component particles.
[0031] Suitable binders and binder systems include acrylic polymers, polyolefins, cellulose esters, cellulose acetate, cellulose triacetate, cellulose propionate, cellulose butyrate, cellulose propionate acetate, cellulose butyrate acetate, cellulose propionate butyrate, cyclic olefin copolymers, ethylene methyl acrylate copolymers, polycarbonates, polypropylene, polystyrene, styrene-butadiene copolymers or blends, polyethylene, ethylene / propylene copolymers, polyvinyl acetate (PVA), ethylene vinyl acetate (EVA), PVA-EVA copolymers, ethylene vinyl alcohol copolymers, polyvinylpyrrolidone, polyurethanes, poly(lactic acid), copolyesters, and mixtures thereof.
[0032] The relative concentration of binders (and optionally, viscosity modifiers, plasticizers, biocides, lubricants, defoamers, etc.) to elements that do not change their morphology (e.g., molten flow / film morphology) or evaporate during the coating and drying process is defined by the pigment volume concentration (PVC). PVC is a well-known measure in coating formulations that determines how much binder and "pigment" ("pigment" is defined as particles, fillers, or other elements that do not change during the coating and drying process) should be incorporated into the formulation to achieve a specific porosity in the coating. Typically, a porous coating has a pigment volume concentration of >85%, defined by the formula PVC = [ΣVp / (ΣVp+ΣVb)] × 100% (where ΣVp is the sum of the volumes of all "pigments" in the system and ΣVb is the sum of the volumes of all binders in the system). Those skilled in the art know that if the properties of the binder are compatible with the interfacial chemistry of the pigment (i.e., particles, fillers, etc.), a compatible binder-particle system should be selected.
[0033] In this specification, PVC in the range of about 87% to 97% is suitable for the specified applications of binders used in coatings with average strength or higher, and weaker binders can support lower PVC than stronger binders. In certain specific embodiments, the preferred PVC is about 93%. Binder strength also affects the robustness of the coating to manufacturing stress. In some embodiments, the PVC in the permeable unfolding layer is about 87% to 97%, for example, about 87% to 93%, about 89% to 97%, about 90% to 95%, about 91% to 96%, etc., expressing about 87% to 97% individually as percentages.
[0034] In some embodiments, the binder may be included in the permeable developing layer in any amount to obtain the desired properties. For example, in one embodiment, the binder may be included in amounts such as about 0.1% to 10% by weight, or about 0.5% to 9% by weight, or about 1.0% to 8% by weight, or about 1.5% to 7% by weight, or about 2.0% to 7% by weight, or about 2.5% to 7% by weight, or about 3.0% to 6% by weight, or about 0.5% to 8% by weight, or about 0.5% to 6% by weight, or about 1.5% to 8% by weight, or about 2.5% to 6% by weight, or about 1.0% to 5% by weight, or about 3% to 10% by weight, or about 3.5% to 8% by weight, or about 3% to 7% by weight, or about 4% to 10% by weight, or about 4% to 8% by weight, or about 4% to 6% by weight.
[0035] In some embodiments, the permeable deployment layer includes a combination of preferred features described herein. For example, in some embodiments, the permeable deployment includes hollow glass microspheres having a grinding strength of at least 250 psi, or an average particle size of about 5 μm to 180 μm, or a density of 0.15 g / cc to 0.83 g / cc; in some embodiments, it includes hollow glass microspheres having a grinding strength of at least 250 psi, an average particle size of about 5 μm to 180 μm, and a density of 0.15 g / cc to 0.83 g / cc. In other embodiments, the permeable deployment layer includes hollow glass microspheres having a grinding strength of at least 500 psi, or an average particle size of 20 μm to 65 μm, or a density of 0.3 g / cc to 0.6 g / cc; in other embodiments, it includes hollow glass microspheres having a grinding strength of at least 500 psi, an average particle size of 20 μm to 65 μm, and a density of 0.3 g / cc to 0.6 g / cc.
[0036] In some embodiments, the permeable unfolding layer comprises a polymer binder composition containing about 0.1 to 10% by weight of one or more acrylic polymers, polyolefins, cellulose esters, cellulose acetate, cellulose triacetate, cellulose propionate, cellulose butyrate, cellulose propionate acetate, cellulose butyrate acetate, cellulose propionate butyrate, cyclic olefin copolymers, ethylene methyl acrylate copolymers, polycarbonates, polypropylenes, polystyrene, styrene-butadiene copolymers or blends thereof, polyethylene, ethylene / propylene copolymers, polyvinyl acetate (PVA), ethylene vinyl acetate (EVA), PVA-EVA copolymers, ethylene vinyl alcohol copolymers, polyvinylpyrrolidone, polyurethanes, poly(lactic acid), copolyesters, or mixtures thereof, and hollow glass microspheres present in about 1 to 80% by weight. In some embodiments, the polymer binder is present in an amount of about 2-8% by weight and the hollow glass microspheres in an amount of about 10-60% by weight, while in other embodiments, the polymer binder is present in an amount of about 2-8% by weight and the hollow glass microspheres in an amount of about 20-50% by weight. In other embodiments, the polymer binder is present in an amount of about 3-7% by weight and the hollow glass microspheres in an amount of about 25-45% by weight, while in other embodiments, the polymer binder comprises an acrylic polymer, polyvinyl acetate (PVA) polymer, ethylene vinyl acetate (EVA) polymer, PVA-EVA copolymer, styrene butadiene copolymer, or a mixture thereof, and is present in an amount of about 5-6% by weight, with the hollow glass microspheres present in an amount of about 30-40% by weight. In some embodiments, the permeable developing layer contains about 1-80% by weight of hollow glass microspheres and the pigment volume concentration (PVC) is about 87-97%. In some embodiments, hollow glass microspheres are present at approximately 10-60% by weight and PVC at approximately 87-97%, while in other embodiments, hollow glass microspheres are present at approximately 20-50% by weight and PVC at approximately 87-97%.In other embodiments, hollow glass microspheres are present at approximately 25-45% by weight and PVC at approximately 87-97%, while in some embodiments, the polymer binder comprises an acrylic polymer, polyvinyl acetate (PVA) polymer, ethylene vinyl acetate (EVA) polymer, PVA-EVA copolymer, styrene butadiene copolymer, or a mixture thereof, with hollow glass microspheres present at approximately 30-40% by weight and PVC at approximately 90-95%. In some embodiments, the polymer binder comprises one or more acrylic polymers or copolymers, with hollow glass microspheres present at approximately 30-40% by weight and PVC at approximately 90-95%.
[0037] Permeable developing layers can be prepared by coating with a colloid, suspension, or dispersion mixture. The range of materials useful for inclusion in any permeable developing layer varies considerably, as discussed herein, and typically mainly consists of materials that are resistant to contact with water or other liquids during analysis, i.e., substantially insoluble and non-swelling. Swelling of about 5–25 percent of the dry thickness of the layer may be normal. The thickness of the permeable layer is variable and depends, for example, on the desired sample volume and the void volume of the permeable layer. Typically, a permeable layer is designed to absorb a desired sample volume, and therefore, a permeable layer with a smaller void volume will be thicker to absorb a given sample volume than a layer with a larger void volume. Developing layers with a dry thickness of about 100 μm to about 400 μm (e.g., about 100 μm to about 300 μm or about 125 μm to about 275 μm) are often suitable for absorbing a typical sample volume. However, larger variations in thickness are acceptable, and for example, a thickness of approximately 100 μm to 500 μm may be desirable for a particular development layer.
[0038] The permeable unfolding layer of this disclosure can be pre-formed as a separate layer and then laminated with one or more additional functional layers (e.g., a reagent layer, a filtration layer, a isolation layer, an indicator layer, a physical support layer, etc.) to produce a dry chemical analysis element. If the pre-formed layer as a separate component is coatable, it is typically coated from a solution or dispersion onto a surface from which the layer can be physically peeled off when dry.
[0039] An alternative and more convenient procedure involves sequentially coating each layer within the dry chemical analysis element onto the exfoliation surface or support layer, from bottom to top. Such coatings can be achieved in a continuous or individual process using one or more coating techniques, including, among others, knife-over-air coating (floating knife), knife-over-roll coating, roll coating, kiss coating, gravure coating, measuring rod or Meyer bar coating, comma direct coating, comma reverse coating, reverse roll coating, slot die coating, immersion or dip coating, and curtain coating. It is possible to coat adjacent layers simultaneously using hopper coating techniques. If discreteness of adjacent layers is essential or desired, and maintaining layer separation by adjusting the coating formulation is unsatisfactory, then, as with permeable unfolding layers, appropriate selection of the components of each layer, including the solvent or dispersion medium, can minimize or eliminate undesirable interlayer migration and solvent effects, thereby promoting the formation of distinct discontinuous layers. In addition, one or more layers can be dried for a sufficient time to prevent or minimize mixing with subsequently coated layers. All of these interlayer adhesion problems can be overcome by surface treatment.
[0040] These dry chemical analysis elements may include one or more permeable expansion layers combined with one or more additional functional layers.
[0041] For example, in embodiments including support layers in the form of an optically transparent substrate, knife-over-air coating can be used to apply each layer sequentially. The knife-over-air coating process includes a knife or blade positioned vertically above a substrate supported on both sides by two rollers. The coating weight using this technique is derived from the distance between the two rollers and the tension of the substrate. Raising and lowering the blade also affects the coating weight and penetration level, influencing adhesion and feel by applying additional tension. Knife-over-air coating involves positioning the blade above a substrate supported by a lower roller. Raising and lowering the blade can yield different coating thicknesses, and changing the blade's shape can capture the viscosity and rheology of the coating medium.
[0042] In some embodiments, the permeable unfolding layer further includes one or more components that alter or enhance the functionality of the layer, including, for example, viscosity modifiers (e.g., carboxymethylcellulose), plasticizers (e.g., polyethylene glycol), biocides (e.g., Proclin), lubricants, defoamers (e.g., emulsified silicone), additional particles (or "pigments") in the size range of about 1 to 100 μm, and combinations thereof.
[0043] particle In some embodiments, the particulate material used to form a permeable unfolding layer and provide porosity includes hollow glass microspheres (e.g., also called glass bubbles, hollow glass spheres, balls, bubbles, or microballoons). The hollow glass microspheres of the present disclosure differ from solid glass microspheres (or solid glass spheres, solid glass beads, etc.) in that solid glass microspheres are significantly denser, significantly less reflective (and have a yellowish-brown to yellow hue), and are not hollow. The term “hollow glass microspheres” and its analogues may include different types of glass, e.g., soda-lime glass, borosilicate glass, lead glass, aluminosilicate glass, oxide glass, glass-ceramic glass, non-silicate glass, and polymer glass, as well as other materials having physical properties similar to hollow glass microspheres (e.g., density, reflectivity), and combinations thereof.
[0044] In some embodiments, hollow glass microspheres may be included in the permeable layer in any amount to obtain the desired properties. For example, in one embodiment, the hollow glass microspheres may be included in amounts of 0.1-80% by weight, or 1-80% by weight, or 0.5-70% by weight, or 1-60% by weight, or 1-50% by weight, or 1-40% by weight, or 1-30% by weight, or 1-20% by weight, or 1-15% by weight, or 1-10% by weight, or 5-80% by weight, or 5-70% by weight, or 5-60% by weight, or 5-50% by weight, or 5-40% by weight, or 5-30% by weight, or 5-20% by weight, or 5-15% by weight, or 5-10% by weight, or 10-80% by weight, or 10-70% by weight, or 10-60% by weight, or 10-50% by weight, or 10-40% by weight, and or it is included in amounts of 10-30% by weight, or 10-20% by weight, or 10-15% by weight, or 20-80% by weight, or 20-70% by weight, or 20-60% by weight, or 20-50% by weight, or 20-40% by weight, or 20-30% by weight, or 30-80% by weight, or 30-70% by weight, or 30-60% by weight, or 30-50% by weight, or about 25-45%, or 30-40% by weight, or 40-80% by weight, or 40-70% by weight, or 40-60% by weight, or 40-50% by weight, or 50-80% by weight, or 50-70% by weight, or 50-60% by weight, or 60-80% by weight, or 60-70% by weight. In some embodiments, hollow glass microspheres are included in amounts of 10-50% by weight. In some embodiments, hollow glass microspheres are included in an amount of 15 to 45% by weight. In some embodiments, hollow glass microspheres are included in an amount of 20 to 40% by weight. In some embodiments, hollow glass microspheres are included in an amount of 70% by weight or more. In some embodiments, hollow glass microspheres are included in an amount of 60% by weight or more. In some embodiments, hollow glass microspheres are included in an amount of 50% by weight or more. In some embodiments, hollow glass microspheres are included in an amount of 40% by weight or more. In some embodiments, hollow glass microspheres are included in an amount of 30% by weight or more. In some embodiments, hollow glass microspheres are included in an amount of 20% by weight or more. In some embodiments, hollow glass microspheres are included in an amount of 10% by weight or more.In some embodiments, hollow glass microspheres are included in an amount of 5% by weight or more.
[0045] In this disclosure, preferred hollow glass microspheres are typically spherical microparticles with a diameter in the range of approximately 1 μm to 300 μm. In some embodiments, the hollow glass microspheres have particle sizes (D50 microns or volume microns) of approximately 1 to 200 μm, or approximately 2 to 200 μm, or approximately 5 to 180 μm, or approximately 15 to 135 μm. In some embodiments, the hollow glass microspheres are approximately 1-120 μm, or approximately 10-110 μm, approximately 10-100 μm, or approximately 10-90 μm, or approximately 10-80 μm, or approximately 10-70 μm, or approximately 10-60 μm, or approximately 15 μm-100 μm, or approximately 15 μm-80 μm, or approximately 20-120 μm, or approximately 20-110 μm, or approximately 20-100 μm, or approximately 20-90 μm, or approximately 20- The particles have a size of 80 μm, or approximately 20-70 μm, or approximately 25-120 μm, or approximately 25-110 μm, or approximately 25-100 μm, or approximately 25-90 μm, or approximately 25-80 μm, or approximately 25-70 μm, or approximately 25-60 μm, or approximately 12-40 μm, or approximately 12-30 μm, approximately 13-35 μm, approximately 15-30 μm, approximately 15-35 μm, or approximately 20-30 μm or approximately 20-40 μm.
[0046] In some embodiments, the hollow glass microspheres have an arithmetic mean (average) or median particle size of approximately 5 μm, or approximately 10 μm, or approximately 15 μm, or approximately 20 μm, or approximately 25 μm, or approximately 30 μm, or approximately 35 μm, or approximately 40 μm, or approximately 45 μm, or approximately 50 μm, or approximately 55 μm, or approximately 60 μm, or approximately 65 μm, or approximately 70 μm, or approximately 75 μm, or approximately 80 μm, or approximately 85 μm, or approximately 90 μm, or approximately 95 μm, or approximately 100 μm, or approximately 105 μm, or approximately 110 μm, or approximately 115 μm, or approximately 120 μm.
[0047] In some embodiments, the glass microspheres of the Disclosure are hollow and comprise soda-lime borosilicate glass (e.g., 3M® Glass Bubbles). These hollow glass microspheres are low-density and lightweight while retaining high shatter strength and shear resistance, thereby allowing them to be processed without breakage, for example, through mixers and coaters, to produce porous, permeable thin film coatings with significantly reduced density compared to standard particulate materials, such as pigments. The hollow glass microspheres of the Disclosure have a particle size distribution, surface area-to-volume ratio, and density that lead to the formation of a uniform, permeable unfolding layer that avoids other problems associated with higher-density particles, such as creaming, sedimentation, and dust generation.
[0048] In some embodiments, the hollow glass microspheres have a grinding strength of at least 250 psi, or at least 300 psi, or at least 500 psi, or at least 750 psi, or at least 1,000 psi, or at least 2,000 psi, or at least 3,000 psi, or at least 4,000 psi, or at least 5,000 psi, or at least 6,000 psi, or at least 7,000 psi, or at least 10,000 psi, or at least 15,000 psi, or at least 16,000 psi. In some embodiments, the hollow glass microspheres have a grinding strength of 250 psi to 30,000 psi. In some embodiments, the hollow glass microspheres have a grinding strength of 500 psi to 30,000 psi. In some embodiments, the hollow glass microspheres have a grinding strength of 750 psi to 30,000 psi. In some embodiments, the hollow glass microspheres have a crushing strength of 1,000 psi to 30,000 psi. In some embodiments, the hollow glass microspheres have a crushing strength of 5,000 psi to 30,000 psi. In some embodiments, the glass microspheres have a crushing strength of 10,000 psi to 30,000 psi. In another embodiment, the hollow glass microspheres have a crushing strength of 15,000 psi to 28,000 psi. In yet another embodiment, the hollow glass microspheres have a crushing strength of 16,000 psi to 20,000 psi.
[0049] The low-density hollow glass microspheres in this disclosure are chemically stable (e.g., in their unmodified form), non-flammable, non-porous, and have excellent water resistance.
[0050] In some embodiments, hollow glass microspheres suitable for use in this disclosure have a density of approximately 0.1–0.7 g / cc, or approximately 0.15–0.6 g / cc, or approximately 0.2–0.6 g / cc, or approximately 0.25–0.6 g / cc, or approximately 0.25–0.5 g / cc, or approximately 0.25–0.4 g / cc, or approximately 0.1–0.2 g / cc, or approximately 0.13–0.17 g / cc, or approximately 0.18–0.22 g / cc, or approximately The glass microspheres have a density of 0.19-0.25 g / cc, or about 0.23-0.27 g / cc, or about 0.29-0.35 g / cc, or about 0.32-0.38 g / cc, or about 0.34-0.4 g / cc, or about 0.35-0.41 g / cc, or about 0.43-0.49 g / cc, or about 0.57-0.63 g / cc, or about 0.44-0.83 g / cc, or 0.10-0.60 g / cc. In some embodiments, the glass microspheres have a density of about 0.20-0.80 g / cc, 0.30-0.60 g / cc, or about 0.15-0.60 g / cc, or about 0.4-0.5 g / cc, or about 0.2-0.6 g / cc, or about 0.15-0.6 g / cc. In some embodiments, the glass microspheres have a density of approximately 0.4–0.60 g / cc, approximately 0.46–0.6 g / cc, or approximately 0.45–0.6 g / cc.
[0051] In contrast, the typical densities of other particulate materials, such as solid glass microspheres and titanium dioxide, are much higher than those of the hollow glass microspheres used in the permeable unfolding layers of this disclosure, far exceeding 1 g / cc and often exceeding 2 g / cc. Colloids made from such particulate materials exhibit significant processing challenges, including poor particle dispersion and poor particle suspension within the colloid, which result in, for example, creaming, sedimentation, and dust generation due to the heterogeneous composition in the unfolding layer. Reducing the particle size of such particulate materials helps mitigate the described challenges, but smaller particles limit the maximum size of the void space and further restrict the size and composition of liquid sample components that can move through the unfolding layer.
[0052] In some embodiments, after adding hollow glass microspheres to the binder and one or more additional items of choice as described herein, the density of the compounded product is approximately 1.2 g / cc or less, or approximately 1.1 g / cc or less, or approximately 1.0 g / cc or less, or approximately 0.95 g / cc or less, or approximately 0.90 g / cc or less, or approximately 0.85 g / cc or less, or approximately 0.80 g / cc or less, or approximately 0.75 g / cc or less, or approximately The density is 0.70 g / cc or less, or about 0.65 g / cc or less, or about 0.6 g / cc or less, or about 0.55 g / cc or less, or about 1.0 g / cc to 0.50 g / cc, or about 0.95 g / cc to 0.5 g / cc, or about 0.90 g / cc to 0.5 g / cc, or about 0.85 g / cc to 0.5 g / cc, or about 0.80 g / cc to 0.5 g / cc, or about 0.75 g / cc to 0.55 g / cc. The densities of the combined particulate matter, binders, and other optional components described herein typically have a higher density before the addition of hollow glass microspheres.
[0053] In some embodiments, the hollow glass microspheres have a density of 0.10–0.63 g / cc, a particle size of 5–150 μm, and a grinding strength of at least 250 psi. In some embodiments, the hollow glass microspheres have a density of at least 0.3 g / cc, a particle size of about 25–60 μm, and a grinding strength of at least 500 psi. In some embodiments, the hollow glass microspheres have a density of at least 0.35 g / cc, a particle size of about 30–55 μm, and a grinding strength of at least 500 psi. In some embodiments, the hollow glass microspheres have a density of at least 0.35 g / cc, a median particle size of about 35 μm, and a grinding strength of at least 1,000 psi.
[0054] reflectance When optical detection of color or fluorescence is desired, a high reflectivity of the slide is a crucial parameter for increasing the response and reducing optical variation (noise). Not only is the reflectivity of the dry slide important, but the reflectivity of the wet slide after sample application, as well as the difference between the two measurements, are equally, if not more, important. Dry slides typically have high reflectivity due to the voids present between particles. When a sample is applied, these voids are filled, and the optical properties of the particles in the developed layer control the reflectivity. Table 1 shows the difference in reflectivity values for two types of hollow glass microspheres, as well as two other types of microspheres with less desirable optical properties. [Table 1]
[0055] Similarly, Figure 7 shows a graph of the mean absolute reflectance of an exemplary coated unfolded layer containing hollow glass microspheres (solid line) compared to an exemplary coated unfolded layer containing cross-linked polystyrene microspheres (dashed line), which exhibits substantially higher reflectance over the wavelength range.
[0056] In some embodiments, the permeable developing layer is measured in the absence of one or more pigments such as talc, silicon dioxide, titanium dioxide, calcium carbonate, barium sulfate, kaolin, wollastonite, and mica, or in some embodiments, in the presence of them, to be at least about 65%, or at least about 66%, or at least about 67%, or at least about 68%, or at least about 69%, or at least about 70%, or at least about 71%, or at least about 72%, or at least about 73%, or at least about 74%, or at least about 75%, or at least about 76%, or at least about 77%, or at least about 78%, or It has a dry percentage reflectance of at least approximately 79%, or at least approximately 80%, or at least approximately 81%, or at least approximately 82%, or at least approximately 83%, or at least approximately 84%, or at least approximately 85%, or at least approximately 86%, or at least approximately 87%, or at least approximately 88%, or at least approximately 89%, or at least approximately 90%, or at least approximately 95%, or approximately 65% to 95%, or approximately 65% to 90%, or approximately 65% to 85%, or approximately 65% to 80%, or approximately 65% to 75%, or approximately 70% to 95%, or approximately 70% to 90%, or approximately 70% to 85%, or approximately 70% to 80%.
[0057] In some embodiments, the permeable unfolded layer has a wet percentage reflectance of at least about 50%, or at least about 55%, or at least about 60%, or at least about 65%, or at least about 70%, or at least about 75%, or at least about 80%, or at least about 85%, or at least 90%, or about 50% to 95%, or about 55% to 90%, or about 55% to 85%, or about 55% to 80%, or about 55% to 75%, or about 55% to 70%, or about 55% to 65%, or about 60% to 95%, or about 60% to 90%, or about 60% to 85%, or about 60% to 80%, or about 60% to 75%, or about 60% to 70%, or about 60% to 65%, as measured in the absence of one or more pigments, or in the presence of them.
[0058] buffer solution In some embodiments, the permeable development layer may contain one or more buffers. In some embodiments, the buffer is a basic buffer and has a pH of approximately pH 7 to pH 10, pH 7 to pH 9, pH 7 to pH 8, pH 8 to pH 10, pH 8 to pH 9, pH 7.5 to pH 10, pH 7.5 to pH 9.5, pH 7.5 to pH 9, pH 7.5 to pH 8.5, pH 8 to pH 10, pH 8 to pH 9.5, pH 8 to pH 9, or one of approximately pH 7, pH 7.5, pH 8, pH 8.4, pH 9, pH 9.5, or pH 10. In some embodiments, the permeable development layer is dried in a buffer with a pH of approximately pH 7 to 9.
[0059] Suitable basic buffers include, for example, MOPS (3-(N-morpholino)propanesulfonic acid), HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid), TES (N-tris(hydroxymethyl)methyl-2-aminoethanesulfonic acid), MOBS (4-(N-morpholino)butanesulfonic acid), DIPSO (3-(N,N-bis[2-hydroxyethyl]amino)-2-hydroxypropanesulfonic acid), TAPSO (N-[tris(hydroxymethyl)methyl]-3-amino-2-hydroxypropanesulfonic acid), T EA (triethanolamine), pyrophosphate (pKa4), HEPPSO (N-(2-hydroxyethyl)piperazine-N'-2-hydroxypropanesulfonic acid), POPSO (pyrazine-N,N'-bis(2-hydroxypropanesulfonic acid)), tricine, hydrazine, glycylglycine (pKa2), Trizma (tris), EPPS (N-(2-hydroxyethyl)piperazine-N'-(3-propanesulfonic acid)), HEPPS (4-(2-hydroxyethyl)piperazine-1-propanesulfonic acid), bicine (N,N-bis(2-Hyd (Loxyethyl)glycine), HEPBS (4-[4-(2-hydroxyethyl)piperazine-1-yl]butane-1-sulfonic acid), TAPS (3-{[1,3-dihydroxy-2-(hydroxymethyl)propane-2-yl]amino}propane-1-sulfonic acid), AMPD (2-amino-2-methyl-1,3-propanediol), TABS (N-tris(hydroxymethyl)methyl-4-aminobutanesulfonic acid), AMPSO (N-(1,1-dimethyl-2-hydroxyethyl)-3-amino-2-hydroxypropanesulfonic acid), taurine ( Examples include AES, borates (pKa1, pKa2, or pKa3), CHES (2-(cyclohexylamino)ethane-1-sulfonic acid), AMP (2-amino-2-methyl-1-propanol), glycine (pKa2), ammonium hydroxide, CAPSO (3-(cyclohexylamino)-2-hydroxy-1-propanesulfonic acid), carbonates (pKa2), methylamine, piperazine (pKa2), CAPS (3-(cyclohexylamino)-1-propanesulfonic acid), and others suitable for supporting biological reactions at basic pH levels.pKa1 represents the negative common logarithm of the primary (lowest) acid dissociation constant (Ka) of the solution, while pKa2 (pKa3, etc.) represents the negative common logarithm of the secondary (tertiary, etc.) acid dissociation constant (Ka) of the solution, where two (three, etc.) dissociations may occur. Suitable pH buffering behavior is generally observed within + / - 1 units of the pKa value, and therefore, buffers with pKa values of 7 or higher may be suitable for permeable developing layers.
[0060] In certain embodiments, the permeable developing layer contains bicine buffer at pH 8.4. Generally, the amount of basic buffer is 1 to 50 mg / ml, for example, 5 to 45 mg / ml, 10 to 30 mg / ml, or 15 to 25 mg / ml.
[0061] In some embodiments, the permeable development layer further contains an acidic buffer. In some embodiments, the pH is approximately pH 1 to pH 6, pH 1 to pH 5, pH 2 to pH 7, pH 2 to pH 6, pH 3 to pH 6, pH 4 to pH 6, pH 2 to pH 5, pH 3 to pH 5, pH 2.5 to pH 5, pH 2.5 to pH 5, pH 2.5 to pH 4.5, pH 3 to pH 5.5, pH 3.5 to pH 5, or one of approximately pH 2.5, pH 3, pH 3.5, pH 4, pH 4.5, pH 5, pH 5.5, or pH 6. In certain embodiments, the pH is approximately pH 3.5 to pH 4.5, and in other specific embodiments, the pH of the permeable development layer is approximately pH 4.
[0062] Suitable acidic buffers include, for example, maleate (pKa1), phosphate (pKa1), glycine (pKa1), citrate (pKa1), glycylglycine (pKa1), malate (pKa1), formate, citrate (pKa2), succinate (pKa1), acetate, propionate, malate (pKa2), pyridine, piperazine (pKa1), cacodylate, succinate (pKa2), MES (2-(N-morpholino)ethanesulfonic acid), citrate (pKa3), maleate (pKa2), bistris, carbonate (pKa1) Examples include PIPES (piperazine-N,N'-bis(2-ethanesulfonic acid), ACES (N-(2-acetamide)-2-aminoethanesulfonic acid), tartrates, and others suitable for supporting biological reactions at acidic pH levels. Suitable pH buffering behavior is generally observed within + / - 1 unit of pKa value, and therefore buffers with pKa values less than 7 may be suitable for the permeable development layer. Generally, the amount of acidic buffer is 1-50 mg / ml, e.g., 5-45 mg / ml, 10-30 mg / ml, or 15-25 mg / ml.
[0063] Additional void-forming agent In some embodiments of this disclosure, the permeable unfolding layer may further include additional void-forming agents dispersed therein. In one embodiment, suitable additional void-forming agents include at least one polymer selected from acrylic polymers, cellulosic polymers, starch, esterified starch, polyketones, polyesters, polyamides, polysulfones, polyimides, polycarbonates, olefin polymers, and copolymers thereof. As used herein, the term “olefin polymer” is intended to mean polymers resulting from the addition polymerization of ethylenically unsaturated monomers, such as polyethylene, polypropylene, polystyrene, poly(acrylonitrile), poly(acrylamide), acrylic polymers, poly(vinyl acetate), poly(vinyl chloride), and copolymers thereof. The additional void-forming agents may also include one or more inorganic compounds, including talc, silicon dioxide, titanium dioxide, calcium carbonate, barium sulfate, kaolin, wollastonite, and pigments such as mica. The additional void-forming agents may also include combinations of polymeric and inorganic materials.
[0064] surfactant In some embodiments, the permeable development layer further comprises one or more surfactants. The surfactants may be effective, for example, in normalizing liquid transport within the permeable development layer. Normalizing liquid transport refers to obtaining equivalent permeation of the solvent and the dissolved components of various applied samples in the permeable development layer, despite variations in protein concentration between such samples.
[0065] A wide range of ionic and nonionic surfactants may be useful. Suitable surfactants include those with a hydrophilic-lipophilic balance (HLB) in the range of approximately 6 to 15. HLB is a measure of the degree of hydrophilicity or lipophilicity, and is given by the formula HLB = 20 * M h / M(where M hThe HLB is determined by calculating the ratio of the molecular weights of the hydrophilic and lipophilic portions of a surfactant molecule according to the molecular weight of the hydrophilic portion (where HLB is the molecular weight of the hydrophilic portion of the molecule and M is the molecular weight of the entire molecule), and results are obtained on a scale of 0 to 20. An HLB value of 0 corresponds to a completely lipophilic / hydrophobic molecule, and a value of 20 corresponds to a completely hydrophilic / hydrophobic molecule. Suitable surfactants may have a carboxyl group, a sulfonic acid group, a sulfate group, or a phosphate as the hydrophilic group. Examples of anionic surfactants having a sulfonic acid group include alkylbenzene sulfonates (e.g., sodium dodecylbenzenesulfonate; SDBS), alkylnaphthalene sulfonates, alkyl sulfates, polyoxyethylene alkyl ether sulfates, α-olefin sulfonates, and N-acylmethyl taurates.
[0066] In some embodiments, the surfactant is an alkylbenzene sulfonate having an alkyl chain containing 10 to 14 carbon atoms, and in some embodiments, sodium dodecylbenzenesulfonate is used. As the salt, sodium salt is the most common, but potassium salt or lithium salt can also be used.
[0067] In some embodiments, one or more surfactants include nonionic surfactants such as ethoxylates, fatty alcohol ethoxylates, alkylphenol ethoxylates (APE or APEO), fatty acid ethoxylates, ethoxylated amines and / or fatty acid amides, terminally blocked ethoxylates, fatty acid esters of polyhydroxy compounds, fatty acid esters of glycerol, fatty acid esters of sorbitol, fatty acid esters of sucrose, and alkyl polyglucosides.
[0068] In some embodiments, the nonionic surfactant is soluble in a polar solvent, which in some embodiments is an alcohol, such as methanol, ethanol, n-propanol, isopropanol, or n-butanol.
[0069] In some embodiments, one or more surfactants may be included in the permeable development layer in an amount effective to normalize the development within the layer. This is typically about 1 percent to about 15 percent. Conversely, unless expressly specified otherwise, references herein to concentration percentages mean the weight percentage of the total solids in the layer in which the specified item is located. It is preferable that the surfactant is provided in the permeable development layer in an amount of about 0.5 percent to about 10 percent, most preferably about 1 percent to about 5 percent. In calculating the surfactant concentration, adjustments should be made for the inactive components in any surfactant composition. Surfactant concentrations expressed in terms of range are typically in the range of about 0.5 to about 5 grams / square meter.
[0070] Viscosity modifier In some embodiments, viscosity modifiers can be used to increase viscosity and provide an additional suspension for the particles. Suitable agents include cellulose and cellulose derivatives (e.g., carbodimethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose), acrylic alkali-swellable polymers, and nonionic polyurethane or polyethylene-associating thickeners. In certain embodiments, the polymer-developed layer contains carboxymethylcellulose.
[0071] plasticizer In some embodiments, plasticizers can be used to increase the flexibility of the coating. The plasticizer is compatible with the optimal solvent system and is the primary binder. g It is characterized as a low molecular weight polymer that reduces [unclear value]. Suitable agents for this application include low molecular weight polyethylene glycol (e.g., PEG-200 to PEG-6000), dicarboxylic acid esters (e.g., citrate esters), fatty acid esters, polypropylene, and polyethylene glycol phenyl ethers. In certain embodiments, one or more of PEG-200 to PEG-600 are included, in other embodiments, one or more of PEG-200 to PEG-400 are included, in some embodiments, PEG-200, PEG-300, or PEG-400 are included, and in some embodiments, PEG-300 is included.
[0072] biocides In some embodiments, biocides can be used to preserve the coating and protect it from microbial contamination. Suitable biocides include those of the isothiazolin family (ProClin® and Kathon® trademarks), as well as other preservatives known to provide biocides, such as sodium azide. In certain embodiments, one or more of ProClin 150, ProClin 200, ProClin 300, or ProClin 950 are included; in some embodiments, ProClin 200 or ProClin 300 are included; and in some embodiments, ProClin 300 is included.
[0073] defoaming agent In some embodiments, defoamers can be used to reduce air incorporated into the coating formulation, thereby improving coating properties and quality. Examples of defoamers include mineral oil or silicone emulsions in water or polyether-based preparations.
[0074] use The permeable deployable layers of this disclosure can be adapted for use in a wide variety of chemical analyses, from clinical chemistry to chemical research and chemical process control laboratories. Such deployable layers are well suited for use in clinical trials of body fluids (e.g., blood, serum, urine) where multiple repeated tests are frequently performed and rapid test results are often required.
[0075] In the field of blood analysis, for example, a multilayer dry chemical analysis element can be prepared by combining one or more permeable developing layers with one or more functional layers, which can be adapted for use in performing quantitative analysis of one or more analytes found in blood. Therefore, for example, the analysis element can be adapted by appropriately selecting test reagents or other interacting materials added to one or more layers, including the permeable developing layers, to analyze albumin, alkaline phosphatase, alanine transaminase (ALT), amylase (AMYL), aspartate (amino)transferase (AST), bile acids, total bilirubin (TBIL), blood urea nitrogen (BUN), calcium, cholesterol, creatine kinase (CK), creatine, C-reactive protein (CRP), fructosamine (FRU), etc. It can be readily applied for use in the analysis of blood components such as gamma-glutamyltransferase (GGT), glucose, potassium, lactate (LAC), lactate dehydrogenase (LDH), lipase (LIPA), magnesium, sodium, ammonia, phenobarbital (PHBR), phosphate (PHOS), progesterone (PROG), symmetric dimethylarginine (SDMA), total protein (TP), triglycerides (TRIG), total thyroxine 4 (TT4), and many other components. Similar arrangements of appropriate layers can be made for other fluids, whether biological or non-biological.
[0076] When analyzing blood using the dry chemical analysis element of this disclosure, blood cells may first be separated from serum, for example by centrifugation, and the serum may be applied to the analysis element. However, when quantifying one or more analytes in a sample using, for example, reflectance spectrophotometric analysis techniques, or when analyzing them by other means, such separation is not always necessary, whether these analytes are detected directly or indirectly through detectable species in layers of the analysis element that respond proportionally to the amount of analytes in the sample.
[0077] One or more liquid samples can be applied directly to the top layer of the dry chemical analysis element, and in some embodiments, this top layer is a permeable development layer. However, the permeable development layer does not have to be the top layer of the analysis element. One or more functional layers that provide other functions, such as (pre)filtration of the liquid sample (e.g., size exclusion to remove larger sample components, or chemical or biological filtration to remove inhibitory or interfering compounds), or replenishment of sample reagents, may be positioned above the permeable development layer.
[0078] This analytical element is used by applying the liquid sample to be analyzed to the upper layer of the analytical element. In some embodiments, a permeable developing layer is positioned as the uppermost layer of the analytical element, and therefore the applied sample comes into contact with the developing layer before any other functional layers below it. The analytical accuracy of the analytical elements described herein is not substantially reduced by variations in the volume of the applied sample when a permeable developing layer is present within the analytical element. As a result, manual or mechanical application of the sample is generally acceptable.
[0079] In an exemplary analytical procedure using a permeable developing layer of this disclosure, the analytical element is positioned to receive a certain amount of sample (e.g., one or more drops) from a dispenser (e.g., a hand-held pipette or an automated dispenser in an automated analyzer). After the application of the sample, and, if the permeable developing layer is not the top layer, after the sample has been received by the permeable developing layer, the analytical element is exposed to any adjustments (e.g., temperature control, humidification, etc.) that may be desirable to standardize, accelerate, or otherwise facilitate obtaining any test results. The sample is developed, mixed, and / or measured by the developing layer into a functional layer beneath the developing layer, and in fluid contact with the developing layer. This can be conveniently achieved by the appropriate selection of various parameters such as layer thickness, void volume, and the like.
[0080] After the analytical results are obtained as detectable changes, the measurement is typically performed by passing the analytical element through a zone provided with equipment suitable for reflectance spectrophotometry. Such equipment guides a beam of energy, such as light, through a functional layer containing an (optically transparent) support and the detectable species. The light is then reflected by a highly reflective, transmissive layer and returned to the detection means. The use of reflectance spectrophotometry can be advantageous in some situations because it effectively avoids interference from residues, such as blood cells, that may remain on or within the layers of the analytical element. Generally, electromagnetic radiation in the range of approximately 200–900 nm has been found useful for such measurements, but any radiation can be used as long as the analytical element is transmissive and the products generated within the element can be quantified. Various calibration techniques can be used to provide a control for the analysis. As an example, to enable the use of differential measurement in the analysis, a sample of the analyte standard solution can be applied adjacent to the area where the sample droplet is placed.
[0081] As is understood, layers (permeable unfolding layers and other functional layers) and analytical elements containing such layers can be configured in various forms, such as coated on slides, as cartridges for use in automated chemical analyzers or instruments, as elongated tapes of any desired width, as sheets, or as chips. A particular analytical element may be adapted for one or more tests of a single type (i.e., one analyte), or for one or more tests of various different test types. In the former embodiment, which involves multiple tests of the same analyte, a common support may be coated with one or more strips or channels, each of the same composition forming a composite analytical element suitable for performing tests in parallel (multiplexing) on multiple liquid samples. In the latter embodiment, a common support may be coated with one or more strips or channels, each of which is optionally different in composition, to form a composite analytical element suitable for performing various different tests.
[0082] In some embodiments, one or more permeable developing layers are combined with one or more functional layers (e.g., a reagent layer, a filtration layer, a isolation layer, an indicator layer, a physical support layer, etc.) to create a dry chemical analysis element. In embodiments, the dry chemical analysis element further includes a support layer that provides a rigid or semi-rigid physical base for the layers of the analysis element.
[0083] In some embodiments, the support layer is optically transparent and impermeable to aqueous liquids, and examples include, for example, a transparent support in the form of a film or sheet having a thickness of 50 μm to 5 mm, and in some embodiments, it includes polymers such as polyethylene terephthalate (PET), polycarbonate of bisphenol A, polystyrene, cellulose esters (e.g., cellulose diacetate, cellulose triacetate, or cellulose propionate acetate), or similar materials, or other suitable materials such as glass. In some embodiments, the support layer is PET.
[0084] The optimal support layer for any particular analytical element is one that conforms to the intended direction of the results. Preferred supports include a radiotransparent support material that transmits electromagnetic radiation in the wavelength range of approximately 200 nm to approximately 900 nm.
[0085] The components of any particular layer of the analytical element, and the optimal order or configuration of the layers, depend on the intended use of the analytical element. As previously mentioned, the pore size of the permeable spreading layer may be selected so that the permeable layer filters out undesirable sample components that would interfere with, for example, the analytical reaction or the detection of any test results generated within the analytical element. For example, in whole blood analysis, a permeable layer with a pore size of 1 to about 5 microns is typically useful for sorting blood cells that are about 7 to about 30 microns in size. If desired, the analytical element may include multiple permeable spreading layers, each of which may differ in its ability to spread, mix, measure, and filter samples. Also, if it is necessary to restrict the transport of substances within the permeable layer beyond what is provided by the permeable layer, a filtration layer or dialysis layer may be included at an appropriate location within the analytical element.
[0086] In some embodiments, the analytical element also includes a primer layer that promotes and / or strengthens the bonding between the other layers of the analytical element and the support layer. Alternatively, or additionally, physical or chemical activation treatments can be performed on the surface of the support layer to enhance adhesion.
[0087] In some embodiments, the primer layer comprises a hydrogel, which is a crosslinked three-dimensional hydrophilic network having the ability to swell but resist dissolution when placed in water or other biological fluids such as D4 hydrogel. In some embodiments, the primer layer also comprises a support matrix such as cellulose and / or cellulose derivatives (e.g., carboxymethylated cellulose, methylated cellulose, hydroxyethylated cellulose, and hydroxypropylated cellulose). In some embodiments, the primer layer comprises D4 hydrogel and cellulose. [Examples]
[0088] Example 1 - Mercury intrusion porosimetry (MIP) Using mercury intrusion porosimetry (MIP), the total pore area, median pore size, total intrusion volume, bulk density, apparent density, and porosity were measured for two samples (one having a coated and developed layer applied to a PET substrate (DuPont's "Melinex"), and the other being a PET substrate alone).
[0089] The pore size distribution and porosity of the sample were analyzed using a mercury intrusion porosimeter, which measures the volume of mercury, a non-wetting liquid, because increasing the pressure and injecting it into the sample allows for the exploration of increasingly smaller pores. The Washburn formula was used to calculate the equivalent internal cylindrical pore diameter based on the applied pressure.
number
[0090] During the ceremony,
number
number
[0091] One strip of PET coated with a 2cm × 10cm developing layer formulation was used for analysis, and two strips of base PET, also measuring 2cm × 10cm, were used for analysis. The experiment was conducted over an operating range of approximately 0.1 psia to approximately 61,000 psia (or over a pore size range of approximately 0.004 μm to 200 μm). A contact angle of 140° was used. For PET coated with the developing layer formulation, the following additional experimental parameters and detailed results apply: sample mass: 0.4276 g; stem volume used: 64%; mercury temperature: 20.83 °C; assembly mass: 134.2171 g; permeability meter volume: 5.6721 mL; total intrusion volume at 50, 148.80 psia: 0.5770 mL / g; total pore area at 50, 148.80 psia: 69.475 m² 2 Median pore size (volume) at 51.35 psia and 0.289 mL / g: 4.19750 μm; 18,675.40 psia and 34.737 μm 2 Median pore size (area) at / g: 0.01154 μm; average pore size (4V / A): 0.03322 μm; bulk density at 1.02 psia: 0.7961 g / mL; apparent (skeleton) density at 50 and 148.80 psia: 1.4726 g / mL; and porosity: 45.9385%.
[0092] For PET base material, the following additional experimental parameters and detailed results apply: sample mass: 0.8055 g; stem volume used: 30%; mercury temperature: 21.06°C; assembly mass: 132.6949 g; permeameter volume: 5.6721 mL; total intrusion volume at 50,149.97 psia: 0.1420 mL / g; total pore area at 50,149.97 psia: 10.064 m 2 / g; median pore diameter (volume) at 8.14 psia and 0.071 mL / g: 26.48438 μm; 32,890.00 psia and 5.032 m 2 / g median pore diameter (area): 0.00655 μm; average pore diameter (4V / A): 0.05644 μm; bulk density at 1.02 psia: 1.1823 g / mL; apparent (skeletal) density at 50,149.97 psia: 1.4208 g / mL; and porosity: 16.7894%.
[0093] The summary results of MIP are shown in Table 2 below and Figures 3 to 12.
Table 2
[0094] Example 2 Formulation of Development Layer Containing Hollow Glass Microspheres To prepare the development layer formulation, 111 g of 250 mM HEPES buffer, 205 g of 1% carboxymethyl cellulose solution (MW 750k), 25 g of deionized water, and 2.238 g of PEG300 were added to a 500 mL glass container. This mixture was stirred at a speed of 200 rpm using a pitched blade impeller in an overhead mixer. Once homogenized, about 0.45 g / cm 3 200 g of hollow glass microspheres having a bulk density of were added slowly over 10 to 15 minutes while mixing at 500 rpm. Once combined, 32 g of emulsified acrylic binder (Hycar® FF 26916, manufactured by Lubrizol) was added to the mixture and allowed to mix for about 5 minutes. After the binder was fully incorporated, the mixing speed was reduced to 100 rpm, 22.08 g of 10% SDBS solution was added, and the mixture was allowed to mix for an additional 5 minutes.
[0095] Example 3 - Application of the developing layer formulation Once prepared, the developing layer formulation can be applied to a suitable substrate using various coating techniques. In one example, the developing layer formulation was applied to the top of a previously coated and dried layer containing a lipid substrate suitable for pancreatic lipase detection. Using a slot die coating applicator, the developing layer formulation was quantitatively dispensed into the slot die by a piston pump and applied to the previously coated layer to a wet thickness of approximately 200 μm. Upon drying, the developing layer forms a continuous, opaque, and reflective coated surface that absorbs and disperses liquid samples and transfers them to the reagent-containing layer below.
[0096] Those skilled in the art will readily understand that this disclosure is well adapted to achieve its purpose and to obtain the outcomes and benefits mentioned, as well as those unique therein. The disclosure described herein is representative of and illustrative of currently preferred embodiments and is not intended to be limited to the scope of this disclosure. Those skilled in the art will know that modifications and other uses therein will occur, encompassing the spirit of this disclosure as defined by the claims. Furthermore, the section headings used herein are for summary purposes only and should not be construed as limiting the subject matter described.
[0097] No reference, including any non-patent or patent documents, cited herein constitutes prior art. In particular, unless otherwise stated, no reference to any document herein constitutes any part of the common general knowledge in the art in the United States or any other country. Any consideration of a reference is limited to the claims of its authors, and the applicant reserves the right to challenge the accuracy and appropriateness of any document cited herein. All references cited herein are incorporated entirely by reference unless otherwise expressly suggested.
[0098] In the event of any discrepancy between the definitions and / or descriptions found in the cited references, this disclosure shall prevail.
Claims
1. A permeable unfolding layer, Hollow glass microspheres, and Contains a polymer binder, The permeable unfolding layer has high reflectivity and low density.
2. The permeable unfolding layer according to claim 1, wherein the polymer binder comprises an emulsifying polymer or copolymer having adhesive properties.
3. The permeable unfolding layer according to claim 1 or 2, wherein the hollow glass microspheres have a diameter of about 1 μm to about 100 μm.
4. The permeable developing layer according to any one of claims 1 to 3, wherein the polymer developing layer has a dry reflectance of at least about 65%, at least about 70%, at least about 75%, at least about 80%, or at least about 85%.
5. The permeable developing layer according to any one of claims 1 to 3, wherein the polymer developing layer has a dry reflectance of about 65% to 85%, about 65% to 80%, or about 65% to 75%.
6. The permeable developing layer according to any one of claims 1 to 5, wherein the polymer developing layer has a wet reflectance of at least about 50%, at least about 55%, at least about 60%, at least about 65%, at least about 70%, at least about 75%, or at least about 80%.
7. The permeable developing layer according to any one of claims 1 to 5, wherein the polymer developing layer has a wet reflectance of about 50% to 85%, about 55% to 80%, about 55% to 75%, or about 55% to 80%.
8. The permeable developing layer according to any one of claims 1 to 7, wherein the polymer developing layer has a density of less than about 1.0 g / cc, less than about 0.9 g / cc, less than about 0.85 g / cc, less than about 0.80 g / cc, less than about 0.75 g / cc, or less than about 0.7 g / cc.
9. The permeable developing layer according to any one of claims 1 to 7, wherein the polymer developing layer has a density of about 0.6 to 0.9 g / cc, or 0.65 to 0.85 g / cc, or 0.7 to 0.8 g / cc.
10. The permeable developing layer according to any one of claims 1 to 9, wherein the polymer developing layer has an average void volume of about 10 percent to about 80 percent.
11. The permeable developing layer according to any one of claims 1 to 9, wherein the polymer developing layer has an average void volume of about 20 percent to about 80 percent, about 30 percent to about 80 percent, or about 40 percent to about 80 percent.
12. The permeable unfolding layer according to any one of claims 1 to 11, wherein the hollow glass microspheres have a pulverization strength of at least 250 psi, or an average particle size of about 5 μm to 180 μm, or a density of 0.15 g / cc to 0.83 g / cc.
13. The permeable unfolding layer according to any one of claims 1 to 11, wherein the hollow glass microspheres have a pulverization strength of at least 250 psi, an average particle size of about 5 μm to 180 μm, and a density of 0.15 g / cc to 0.83 g / cc.
14. The permeable unfolding layer according to any one of claims 1 to 11, wherein the hollow glass microspheres have a pulverization strength of at least 500 psi, or an average particle size of 20 μm to 65 μm, or a density of 0.3 g / cc to 0.6 g / cc.
15. The permeable unfolding layer according to any one of claims 1 to 11, wherein the hollow glass microspheres have a pulverization strength of at least 1000 psi, an average particle size of 20 μm to 65 μm, and a density of 0.3 g / cc to 0.6 g / cc.
16. The polymer binder comprises a polymer composition containing about 0.1 to 10% by weight of one or more acrylic polymers, polyolefins, cellulose esters, cellulose acetate, cellulose triacetate, cellulose propionate, cellulose butyrate, cellulose propionate acetate, cellulose butyrate acetate, cellulose propionate butyrate, cyclic olefin copolymers, ethylene methyl acrylate copolymers, polycarbonates, polypropylenes, polystyrene, styrene-butadiene copolymers or blends, polyethylene, ethylene / propylene copolymers, ethylene vinyl acetate (EVA), ethylene vinyl alcohol copolymers, polyvinylpyrrolidone, polyurethanes, poly(lactic acid), copolyesters, and mixtures thereof, and The permeable unfolding layer according to any one of claims 1 to 15, wherein the hollow glass microspheres are present in an amount of about 1 to 80% by weight.
17. The polymer binder is present in an amount of approximately 2 to 8% by weight, and The permeable unfolding layer according to claim 16, wherein the hollow glass microspheres are present in an amount of about 10 to 60% by weight.
18. The polymer binder is present in an amount of approximately 2 to 8% by weight, and The permeable unfolding layer according to claim 16, wherein the hollow glass microspheres are present in an amount of about 20 to 50% by weight.
19. The polymer binder is present in an amount of approximately 3 to 7% by weight, and The permeable unfolding layer according to claim 16, wherein the hollow glass microspheres are present in an amount of about 25 to 45% by weight.
20. The polymer binder comprises an acrylic polymer, polyvinyl acetate (PVA) polymer, ethylene vinyl acetate (EVA) polymer, PVA-EVA copolymer, styrene-butadiene copolymer, or a mixture thereof, and is present in an amount of about 5-6% by weight, and The permeable unfolding layer according to claim 16, wherein the hollow glass microspheres are present in an amount of about 30 to 40% by weight.
21. The polymer binder comprises a polymer composition containing one or more acrylic polymers, polyolefins, cellulose esters, cellulose acetate, cellulose triacetate, cellulose propionate, cellulose butyrate, cellulose propionate acetate, cellulose butyrate acetate, cellulose propionate butyrate, cyclic olefin copolymers, ethylene methyl acrylate copolymers, polycarbonates, polypropylenes, polystyrene, styrene-butadiene copolymers or blends, polyethylene, ethylene / propylene copolymers, ethylene vinyl acetate (EVA), ethylene vinyl alcohol copolymers, polyvinylpyrrolidone, polyurethanes, poly(lactic acid), copolyesters, and mixtures thereof. The aforementioned hollow glass microspheres are present in an amount of approximately 1 to 80% by weight. A permeable unfolding layer according to any one of claims 1 to 15, wherein the pigment volume concentration (PVC) is approximately 87% to 97%.
22. The aforementioned hollow glass microspheres are present in an amount of approximately 10 to 60% by weight, and The permeable developing layer according to claim 21, wherein the pigment volume concentration (PVC) is approximately 87% to 97%.
23. The aforementioned hollow glass microspheres are present in an amount of approximately 20 to 50% by weight, and The permeable developing layer according to claim 21, wherein the pigment volume concentration (PVC) is approximately 87% to 97%.
24. The aforementioned hollow glass microspheres are present in an amount of approximately 25 to 45% by weight, and The permeable developing layer according to claim 21, wherein the pigment volume concentration (PVC) is approximately 87% to 97%.
25. The polymer binder includes an acrylic polymer, a polyvinyl acetate (PVA) polymer, an ethylene vinyl acetate (EVA) polymer, a PVA-EVA copolymer, a styrene-butadiene copolymer, or a mixture thereof. The aforementioned hollow glass microspheres are present in an amount of approximately 30-40% by weight, and The permeable developing layer according to claim 21, wherein the pigment volume concentration (PVC) is approximately 90% to 95%.
26. The polymer binder comprises one or more acrylic polymers, acrylic copolymers, or mixtures thereof. The aforementioned hollow glass microspheres are present in an amount of approximately 30-40% by weight, and The permeable developing layer according to claim 21, wherein the pigment volume concentration (PVC) is approximately 90% to 95%.
27. A permeable developing layer according to any one of claims 1 to 26, further comprising one or more buffers.
28. The permeable developing layer according to claim 27, wherein the buffer solution comprises one or more acidic buffer solutions, basic buffer solutions, or mixtures thereof.
29. The permeable developing layer according to claim 27, wherein the buffer solution comprises one or more of bicine buffer or HEPES buffer.
30. A permeable developing layer according to any one of claims 1 to 29, further comprising one or more surfactants.
31. A permeable developing layer according to any one of claims 1 to 30, further comprising one or more plasticizers.
32. The permeable developing layer according to claim 31, wherein one or more plasticizers include PEG.
33. The permeable unfolding layer according to claim 32, wherein the PEG includes PEG 300.
34. A permeable unfolding layer according to any one of claims 1 to 33, further comprising one or more biocides.
35. A permeable developing layer according to any one of claims 1 to 33, further comprising one or more defoaming agents.
36. A permeable unfolding layer according to any one of claims 1 to 35, further comprising one or more void-forming agents.
37. The permeable developing layer according to claim 36, wherein the void-forming agent comprises a pigment.
38. The permeable unfolding layer according to any one of claims 1 to 37, wherein the layer has a thickness of about 100 μm to about 500 μm, or about 100 μm to about 400 μm, or about 100 μm to about 300 μm.
39. The permeable unfolding layer according to any one of claims 1 to 38, wherein the unfolding layer is isotropically porous.